2008
DOI: 10.1590/s0100-40422008000700004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química de queijo prato por espectroscopia no infravermelho e regressão de mínimos quadrados parciais

Abstract: CaraCterização físiCo-químiCa de queijo prato por espeCtrosCopia no infravermelho e regressão de mínimos quadrados parCiais elenise sauer-leal e fernanda martins okada Departamento de Alimentos, Universidade Tecnológica Federal do Paraná, Campus Ponta Grossa, Av. Monteiro Lobato, s/n -km 04, 84016-210 Ponta Grossa -PR, Brasil patricio peralta-zamora* Departamento de Química, Universidade Federal do Paraná, CP 19081, 81531-990 Curitiba -PR, Brasil Recebido em 11/6/07; aceito em 24/4/08; publicado na web em 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
2
2
1
4
Order By: Relevance
“…A protein content similar to that of the present study was reported by Sauer-Leal and Okada (2008). Values lower than those of the present study were found by Vianna et al (2008) and Roig et al (2003), with protein contents of 22.7 and 18.42%, respectively.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…A protein content similar to that of the present study was reported by Sauer-Leal and Okada (2008). Values lower than those of the present study were found by Vianna et al (2008) and Roig et al (2003), with protein contents of 22.7 and 18.42%, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Values lower than those of the present study were found by Spadoti et al (2005), who evaluated Prato cheese at the 10 th day of maturation, with fat values of 25.33%. A fat value slightly higher than that of the present study was reported by Sauer-Leal and Okada (2008), who evaluated the physico-chemical characterisation of Prato cheese by infrared spectroscopy, with an average of 28.68%.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…[11][12][13] The QSRR models apply to partial least squares(PLS) method often combined with genetic algorithms (GA) for feature selection. 14,15 Because of the complexity of relationships between the property of molecules and structures, nonlinear models are also used to model the structure-property relationships. Nonlinear kernel-based algorithms as kernel partial least squares (KPLS) have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…9 Uma estratégia que vem sendo aplicada com sucesso para superar esses problemas é a utilização conjunta de espectroscopia no infravermelho próximo (NIRS, do inglês near infrared spectroscopy) e calibração multivariada, possibilitando o desenvolvimento de métodos rápidos, de baixo custo, que não usam reagentes ou solventes, praticamente não necessitam de pré-processamento das amostras e não geram resíduos. Nos últimos anos, esta estratégia foi utilizada com sucesso na determinação de diversos parâmetros, como gordura, umidade e proteína, em alguns tipos de queijos e outros derivados de leite, como queijo Danbo, 10 Cheddar, 11 Emmental, 12 Prato, 13 Kefir, 14 queijo fresco 15 e processado. 16 Entretanto, a grande maioria desses trabalhos analisou amostras de um número reduzido de produtores/origens/processos de fabricação, ou mesmo produziu as próprias amostras analisadas, o que não permitiu a incorporação de variância suficiente para o desenvolvimento de modelos adequados ao controle fiscal.…”
unclassified